Uncertainties in AGB evolution and nucleosynthesis. Issue 2 (July 2016) - Lattanzio, John; Karakas, Amanda
Abstract: We summarise the evolution and nucleosynthesis in AGB and Super-AGB stars. We then examine the major sources of uncertainty, especially mass-loss.